2019
DOI: 10.3390/ijms20071543
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid Hormone Disruptors Interfere with Molecular Pathways of Eye Development and Function in Zebrafish

Abstract: The effects of thyroid hormone disrupting chemicals (THDCs) on eye development of zebrafish were investigated. We expected THDC exposure to cause transcriptional changes of vision-related genes, which find their phenotypic anchoring in eye malformations and dysfunction, as observed in our previous studies. Zebrafish were exposed from 0 to 5 days post fertilization (dpf) to either propylthiouracil (PTU), a thyroid hormone synthesis inhibitor, or tetrabromobisphenol-A (TBBPA), which interacts with thyroid hormon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 59 publications
1
31
0
Order By: Relevance
“…Exposure to PTU from 0 to 5 dpf reduced eye size in zebrafish larvae and alters optokinetic responses ( Baumann et al, 2016 ; Gothie et al, 2019 ); effects correlated with PTU-induced downregulation of TR expression ( Baumann et al, 2016 ). Subsequent microarray analysis revealed PTU exposure caused downregulation of phototransduction-related genes coding for opsins, phosphodiesterase, and arrestin ( Baumann et al, 2019 ). In fact, of the genes involved in sensory perception, expression of >90% were found to be downregulated by PTU.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Exposure to PTU from 0 to 5 dpf reduced eye size in zebrafish larvae and alters optokinetic responses ( Baumann et al, 2016 ; Gothie et al, 2019 ); effects correlated with PTU-induced downregulation of TR expression ( Baumann et al, 2016 ). Subsequent microarray analysis revealed PTU exposure caused downregulation of phototransduction-related genes coding for opsins, phosphodiesterase, and arrestin ( Baumann et al, 2019 ). In fact, of the genes involved in sensory perception, expression of >90% were found to be downregulated by PTU.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, of the genes involved in sensory perception, expression of >90% were found to be downregulated by PTU. The number of downregulated genes remained high when measured after a 3-day removal from treatment, though the levels of downregulation were less ( Baumann et al, 2019 ), suggesting differential sensitivity to specific genes and long-term impacts of exposure.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thyroid hormones are important for regulating sensory development in teleost fishes 11,14,36,38 , and our results provide insights into the role they play in this development during recruitment. A. triostegus exhibits an enclosed nose (Supplementary Fig.…”
Section: Discussionmentioning
confidence: 69%
“…Like in amphibians and mammals, also in teleosts the HPT axis is required for normal development and metamorphosis (Carr and Patiño 2011). Several studies already have shown that fish are sensitive to thyroid active substances (Baumann et al 2019;Dang and Kienzler 2019;Stinckens et al 2016). From a risk assessment point of view it would be of interest to know whether the results of (chronic) toxicity tests with fish, which are a standard requirement in various regulatory frameworks, cover the sensitivity of amphibians as well as aquatic species in general.…”
Section: Thyroid Active Chemicalsmentioning
confidence: 99%